CHALLENGES FACED BY LEARNERS WITH LEARNING DISABILITIES WITHIN THE CONTEXT OF INCLUSIVE EDUCATION: A FOCUS ON SIX PRIMARY SCHOOLS IN GLEN VIEW/MUFAKOSE EDUCATION DISTRICT OF ZIMBABWE - SAMKANGE, Dr. Wellington (IJRDO- Journal of Educational Research, 2017)
A global concern for inclusive education has been demonstrated by the different internationalconferences held over the past decades to address issues of equality and equity in education.Some governments have come up with laws and policies that support the implementation ofinclusive education. Inclusivity entails that learners with disabilities learn together with nondisabledlearners. It is important that there are checks and balances on the extent to whichinclusive education is being implemented and how different groups are being catered for inschools. The paper focuses on challenges faced by learners with learning disabilities within thecontext of inclusive education in Glen View/Mufakose district in Harare. The study used themixed methodology and the case study and the descriptive survey designs. Six primary schoolswere purposively sampled. Thirty teachers were randomly sampled and twenty learners withlearning disabilities were opportunistically selected. The study used questionnaires, face-to-faceinterviews and observations to collect data. The study came up with the conclusions that:teachers lacked training in the handling of learners with learning disabilities; learners withlearning disabilities were being wrongly labeled; the use of ability grouping had disadvantagedlearners with learning disabilities; class sizes and lack of supportive devices impeded on thedevelopment of learners with learning disabilities. The study recommends that there has to becapacity building for teachers if the implementation of inclusive education is to be successful. Italso recommends that communities have to mobilize resources to support the implementation ofinclusive education. Lastly the Schools Psychological Services Department has to play a visiblerole in schools.